AN APPRAISAL ANALYSIS OF NEWS REPORTS ON ATTACKING INCIDENTS IN INDONESIA'S NEWSPAPERS: A CASE OF PIKIRAN RAKYAT AND THE JAKARTA POST - Maretha Dwiastuti Putri, - (2018)
This study explores attitude as a language appraisal strategy employed by Indonesia's newspapers in reporting news on attacking incidents. The study aims, firstly, to reveal the types of attitude system employed by Indonesia's local media in news of attacking incidents and, secondly, to investigate the potential meanings that can be inferred from the attitude system. This study follows interpretative−descriptive approach to data collection and analysis. The data were taken from Pikiran Rakyat and The Jakarta Post to give an equal representation of Indonesia's newspapers and analyzed with reference to Martin and White's (2005) Appraisal System focusing on attitude sub-system. The analysis reveals that three sub-systems of attitude (affect, judgment, and appreciation) are employed to deliver positive and negative assessments to different addressees. This strategy is combined with certain organizations of discourse to amplify the intensity of the message that results in modified interpretation and potential meanings from the readers. This approach also works as a tool of stance-taking for the news reporters in viewing the attacking incidents. These results corroborate Nacos and Torres-Reyna's (2003) and Tamborini's (2017) studies that media plays a role in influencing the audience's attitude towards attacking incidents through language use. It is concluded that Indonesia's newspapers insert evaluations towards attacking incidents to modify meanings as a form of media politics.